THE USE OF APHORISMS IN ENGLISH AND UZBEK: A CULTURAL AND LINGUISTIC ANALYSIS - Ahmedova Gulizebo Yakubovna (Ta’limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2025)
Aphorisms, often short and pithy expressions of universal truth or wisdom, are common across languages and cultures. Rooted in centuries of collective experience, they reflect the values, norms, and perspectives of the societies that produce them. This article explores the linguistic and cultural characteristics of aphorisms in English and Uzbek. While both languages use aphorisms to convey philosophical or ethical insights, they differ significantly in form, tone, and cultural meaning. English aphorisms are often brief, ironic, and individualistic, while Uzbek aphorisms are more narrative, collective, and value-driven. Examples from each language are provided to demonstrate how aphorisms convey values and perspectives.